Utlendinger i Norge – norsk innvandringpolitikk, grunner til og følger av migrasjonen (2008) - Lewandowska, Katarzyna (Wydawnictwo Naukowe UAM, 2009)
Migrasjonsfenomenet er et viktig forskningsområdet i moderne norske samfunnsstudier. Grunner til migrasjonsfenomenet er like overalt i verden. Nå for tida har migrasjonen blitt så alminnelig at grenser mellom enkelte land og nasjoner er i ferd med å forsvinne. I tillegg, skaper Internett en følelse av at verden er et ganske lite sted hvor alle kan kommunisere fritt. Artikkelen min har som mål å presentere innvandringsfenomenet med hensyn til Norge. Norge, som ikke er medlem av Den Europeiske Unionen, har sine egne utlendingslov mens landet samarbeider med EU for å utarbeide felles politikk som ville være mest omfattende og mest effektiv. Likevel, i motsetning til en del andre europeiske land, har innvandringsfenomenet i Norge noen særpreg som er knyttet til landets innenriks situasjon og landets plass på Europas kartet, noe som jeg vil skrive videre om. I artikkelen min skal jeg presentere emnet ganske generelt med grunnlag i tilgjengelige statistikker. En betydelig del av informasjoner og tall er hentet fra Internettkilder som gir best oversikt over den nåvarende situasjonen.

The aim of the article is to present the present situation regarding immigrants in Norway. Most of the data that I am using with respect to this matter comes from Internet resources, as most of the statistics are available online only. The moment that can be regarded as crucial for immigrant history in Norway is the late 60ties of the 20th century. Guest workers from Pakistan came to the country invited by the Norwegian government. In 1975 the so called «innvandringsstop» (immigration-stop) regulation was introduced to prevent flooding the country with incoming foreigners. The statistics show that no such significant migration was observed again until 2007-2008 when Polish workers began to come to Norway in large groups. Presently, the largest immigrant groups in Norway are Poles, Pakistani, Germans and Iraqi. There are four important reasons for migration: economic, family, political (refugees) and educational. Work and family are definitely the most common ones. The law concerning immigration was established in 1988 and it is called «Utlendingsforskriften». Moreover, the Norwegian immigration policy respects all the laws and regulations that in force in all the EU countries and that apply to the members of the United Nations organization. Nowadays, the Norwegian government is working on a new immigration law that is planned to be introduced in 2010.
Immigrants in Norway – laws and regulations concerning immigrants; causes and effects on migration (2008)
Keywords: Innvandrere i Norge; Utlendingsforskriften; Immigrants in Norway; Norwegian immigration policy